The perception of Romans (hrōmāyīg) in the Sasanian and Zoroastrian traditions. Issue 1 (2nd January 2022) - Agostini, Domenico
Abstract : The Sasanian and Roman/Byzantine Empires were protagonists in a harsh military confrontation lasting almost four centuries. However, at the same time they built a sophisticated rhetoric of coexistence and a language of diplomacy to pursue their own political goals. While there are many Roman and Byzantine sources describing the Sasanian world, hardly anything is known about how the Sasanians and Zoroastrians perceived the Romans from a cosmological point of view. The shaping of an Iranian identity in Sasanian times demanded the construction of a hostile ''other''. Rome became that "other" and the Iranian and Zoroastrian world's fatal arch-enemy. This article will present and analyze several Iranian and Roman/Byzantine sources with the aim of demonstrating how Sasanians represented themselves as superior to the Romans, while granting them an important role as the main enemy in the context of the cosmological final battle according to the Zoroastrian tradition.